PEMBERIAN JUS KURMA DAN TEH DENGAN PERCEPATAN PERSALINAN KALA I PRIMIGRAVIDA - Nurhidayat Triananinsi; Fadjriah Ohorella; Marlina Azis; Nurfaizah Alza; Jumrah Sudirman; Mudyawati Kamaruddin (JKM (Jurnal Kebidanan Malahayati), 2021)
Background: The first stage of labor can be achieved optimally by trying to get contractions. One of the non-pharmacological treatments used to activate the performance of the oxytocin hormone that stimulates uterine contractions can be carried out by supplying additional food intake. This nutrient consumption is typically in the form of a liquid diet containing glucose or carbohydrates. Date juice and tea (teh kotak) are supposed to contain plenty of carbohydrate to provide liquid nutrition in the form of an energy supplier, and can strengthen the contracted uterine muscles to contract.Purpose: This research was conducted to determine the impact of dates and tea on the smooth progress of the first stage of labor at Kajang Health Center.Methods: This study consisted of the first latent pregnant women at the Kajang HC with the Post-Test-Only design, and a purposive sampling technique found 40 samples. The samples were split into two groups, pregnant women who received 88.8ml of date juice, and who received 600ml of tea during the first stage of labor.  Results: The smoothness of labor was then assessed. This study showed that 75% of pregnant women who got date juice experienced smooth labor and 25% had non-smooth labor. Different to whom were given tea, 20% experienced in smoothness of labor and 80% has been un-smoothly.Conclusion Based on the results of research giving date juice and tea to each group of mothers who gave birth during the first stage of active phase at the Kajang Health Center, Bulukumba, it can be concluded that there is a relationship between the provision of date  juice and the acceleration of labor during the 1st stage of active phase.Suggestions We would like to acknowledge the support of the Directorate of Research and Community Service, Directorate General of Research and Development, Ministry of Research, Technology and Higher Education of the Republic of Indonesia, which support through the Research Grant Program for 2020. We appreciate to Megaresky University and Kajang Health Centre, Bulukumba South Sulawesi for providing services, assistance and cooperation in this study. Keyword: Date Juice, Tea, Smoothness of Labor ABSTRAK Latar Belakang: Persalinan kala I dapat dicapai secara optimal dengan berusaha mendapatkan kontraksi. Salah satu pengobatan nonfarmakologi yang digunakan untuk mengaktifkan kinerja hormon oksitosin yang merangsang kontraksi rahim dapat dilakukan dengan pemberian asupan makanan tambahan. Konsumsi zat gizi ini biasanya berupa makanan cair yang mengandung glukosa atau karbohidrat. Jus kurma dan teh  seharusnya mengandung banyak karbohidrat untuk memberikan nutrisi cair berupa pemasok energi, dan dapat memperkuat otot rahim yang berkontraksi untuk berkontraksi.Tujuan: Penelitian ini dilakukan untuk mengetahui pengaruh kurma dan teh terhadap kelancaran persalinan kala I di Puskesmas Kajang.Metode: Penelitian ini terdiri dari ibu hamil laten pertama di Puskesmas Kajang dengan desain Post-Test-Only, dan teknik purposive sampling didapatkan 40 sampel. Sampel dibagi menjadi dua kelompok, ibu hamil yang menerima 88,8 ml jus kurma, dan yang menerima 600 ml teh selama kala satu persalinan.Hasil: Kelancaran persalinan kemudian dinilai. Penelitian ini menunjukkan bahwa 75% ibu hamil yang mendapat sari kurma mengalami persalinan lancar dan 25% mengalami persalinan tidak lancar. Berbeda dengan yang diberi teh, 20% mengalami kelancaran persalinan dan 80% mengalami tidak lancar.Kesimpulan Berdasarkan hasil penelitian pemberian sari kurma dan teh pada masing-masing kelompok ibu bersalin kala I fase aktif di Puskesmas Kajang Bulukumba dapat disimpulkan bahwa ada hubungan antara pemberian sari kurma dan percepatan persalinan selama kala 1 fase aktif.Saran Kami mengucapkan terima kasih yang sebesar-besarnya atas dukungan Direktorat Riset dan Pengabdian kepada Masyarakat, Direktorat Jenderal Penelitian dan Pengembangan, Kementerian Riset, Teknologi, dan Pendidikan Tinggi Republik Indonesia yang telah mendukung melalui Program Hibah Penelitian Tahun 2020. kepada Universitas Megaresky dan Puskesmas Kajang Bulukumba Sulawesi Selatan yang telah memberikan pelayanan, bantuan dan kerjasamanya dalam penelitian ini. Kata kunci : Jus Kurma, Teh, Kelancaran Persalinan